Design trees: providing roots for revision in design-based research. (2017) - Reinholz, Daniel L.
This paper introduces design trees as a methodological tool to facilitate design-based research. Traditionally, design-based research is conceptualised as a bridge between theory and practice. Yet, theory rarely specifies practice directly, so this makes documenting revision through design a challenge. In contrast, design trees consider theory and practice as two interwoven strands through five levels of specification: 1) frameworks; 2) principles; 3) conjectures; 4) instruction; 5) assessment. Each general level constrains, but does not determine, the more-specific levels. As such, researchers need to be explicit about the decisions they make in prospect (i.e., the path they choose along the tree), so that they can follow the path in retrospect in analysis. This supports researchers to contribute to theory and practice systematically. Two case studies, knowledge integration and complex instruction are used to illustrate design trees.